Research Progress on the Effect of Polysaccharides on the Structure and Quality of High-Moisture Extruded Plant Protein-Based Meat Analogues - ZHANG Tian, HUANG Yuyang, LIU Linlin, LÜ Mingshou, ZHU Ying, SUN Bingyu, ZHU Xiuqing (Shipin Kexue)
High-moisture extrusion is a technology to prepare textured plant protein by high temperature, high pressure and high shear force. With its environmentally friendly, health and nutritional advantages, high-moisture extrusion has become the major technique to produce plant protein-based meat analogues. However, there is still a gap with meat in texture, taste and color, so improving the quality of high-moisture extruded plant protein-based meat analogues has become the focus of attention from researchers and producers. Polysaccharides are often used as texture modifiers in high-moisture extrusion processing. This paper focuses on the effects of several polysaccharides such as starch, gum and dietary fiber on the quality and structure of high-moisture extruded plant protein-based meat analogues, and summarizes the interaction mechanism between polysaccharides and proteins during the extrusion process. This review aims to tap the application potential of polysaccharides in the production of high-moisture extruded plant protein-based meat analogues in order to develop more plant protein-based meat analogues with improved quality using polysaccharides and to achieve improvement in the nutrition and quality of plant protein-based meat analogues.